The Implementation of Google Drive in Synchronizing and Backing Up Data for Lecturers of the Faculty of Islamic Economics and Business, IAIN Lhokseumawe - Abdul Majid, Basrul; Mukhtasar; Husni (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2025)
The Google Drive training program for lecturers at the Faculty of Islamic Economics and Business (FEBI), IAIN Lhokseumawe, was designed to enhance digital literacy and work efficiency in managing academic and administrative data. The program encompassed technical training, monitoring, evaluation, and ongoing mentoring to ensure the sustainable adoption of the application. Evaluation results demonstrated that the training had a significant impact, particularly in supporting tasks such as cloud-based data storage, cross-device synchronization, real-time collaboration, and accreditation data management which require substantial storage capacity and high accessibility. The mentoring program was subsequently extended to lecturers from other faculties at IAIN Lhokseumawe, broadening the training’s benefits. Given its success, the Google Drive training represents a strategic step in supporting digital transformation within the academic environment, fostering a modern, efficient, secure, and integrated workflow system.